Penguatan Kapasitas Komite Sekolah untuk Meningkatkan Peran Aktifnya dalam Peningkatan Kualitas Pendidikan di Wonosobo, Jawa Tengah - Haryanto, Sri; Rohani, Edi; Astuti, Erna Dwi (JOURNAL OF PHILANTHROPY: The Journal of Community Service, 2025)
School Committee Empowerment in Wonosobo Regency is an initiative designed to enhance the strategic role of school committees in education management. School committees in Wonosobo Regency face several problems such as a lack of understanding of their functions and responsibilities, as well as minimal involvement in decision-making related to education policies. The target of this community service involves 35 representatives from junior high school/Islamic junior high school committees in Wonosobo Regency. Through this empowerment program, it is hoped that school committee representatives will gain the knowledge and skills needed to improve the effectiveness of education management in their respective institutions. This community service uses a participatory approach by combining Focus Group Discussions (FGD) and Sharing Best Practices sessions. This program focuses on capacity building through training, collaboration, and innovation to improve the effectiveness of school committees in supporting schools. The results of the study showed a significant increase in participants' understanding of their responsibilities and active involvement in strategic decision-making, especially related to curriculum development and improving school facilities. This program also strengthens the relationship between schools, parents, and the community, creating a solid network to support a more conducive learning environment. Participant feedback confirms that relevant and applicable training not only increases knowledge, but also builds confidence and collaboration skills. This Community Service has a positive impact on the quality of education by encouraging inclusive decision-making, strengthening school accountability, promoting innovation in teaching methods, and increasing student motivation and achievement. This program is a model that can be applied in other areas to empower school committees, while supporting the creation of a more inclusive, sustainable, and community-oriented education system.